E‐Textbooks. Issue 6 (9th February 2015) - Dobler, Elizabeth
Abstract This article explores the digital reading preferences and strategies used by preservice teachers when reading an e‐textbook in a literacy methods course. The use of e‐textbooks is becoming more prevalent due to an increase in access to mobile devices, acceptance of e‐books in general, and the high cost of print textbooks. To ensure comprehension, teachers need an awareness of e‐textbook features and the processes for effectively reading text with embedded web links, video clips, and audio files. In this study, some participants described an increase in cognitive engagement due to the ability to both utilize e‐textbook features and engage with media, in addition to text. Others found the process of reading an e‐textbook challenging because of distractions on their device, eye strain, and a feeling of being overwhelmed with choices. Overall the preservice teachers expressed a preference for choice between using print, electronic format, or both.